Fault Detection and Diagnosis in Air Handling Units with a Novel Integrated Decision Tree Algorithm - Balasubramaniam, Vivekanadam (Journal of Trends in Computer Science and Smart Technology, 2021)
In air handling units (AHUs), wide attention has been attracted by data-driven fault detection and diagnosis techniques as the need for high-level expert knowledge of the concerned system is eliminated. In AHUs, decision tree induction is performed by means of classification and regression tree algorithm which is a data-driven diagnostic strategy based on decision tree. Expert knowledge as well as testing data may be used for validation of fault diagnosis reliability with easy interpretation and understanding ability offered by the decision tree. The diagnostic strategy established and its interpretability are increased by incorporating a regression model and steady-state detector with the model. ASHRAE, Oak Ridge National Lab (ORNL), National Renewable Energy Lab (NREL), Pacific Northwest National Lab (PNNL) and Lawrence Berkeley National Lab (LBNL) datasets are used for validation of the proposed strategy. High average F-measure and improved diagnostic performance may be achieved with this strategy. There is a compliance between the expert knowledge and certain diagnostic rules generated in the decision tree as seen from the expert knowledge implemented diagnostic decision tree interpretation. Based on the interpretation, it is evident that certain diagnostic rules are valid only under specific operating conditions and some of the generated diagnostic rules are not reliable. Data driven models are used for emphasizing the significance of interpretability of fault diagnostic models.
Keywords: Interpretation; Fault Diagnosis; Air Handling Unit; Decision Tree; Feature selection; Fault Detection